Educators in Puerto Rican Juvenile Correctional Institutions: Challenges and Professional Development Needs - Adalberto Santa Olmeda; Ángel A Villafañe Santiago; Manuel Capella Casellas (Universidad Nacional, Costa Rica, 2014)
The main purpose of the present research was to report the experiences of teachers in juvenile correctional institutions, their challenges, and professional development needs. Research was conducted using a qualitative descriptive phenomenological methodology through a semi-structured interview applied to four teachers from the Juvenile Correctional Institutions Administration (AIJ) in Puerto Rico. The information was analyzed based on the systematic qualitative research procedures proposed by Strauss and Corbin (1998), cited by Lucca and Berríos (2003): open, axial and selective coding, respectively. Teachers were greatly satisfied for providing educational services. A relevant finding is the lack of a curriculum that fits the needs of this youth population. The curriculum used is the same as the one used in public schools, which makes it unappealing to these students. These teachers face unusual challenges, including the institutions' security system and the teaching and learning methodology. A lack of coordination is perceived in the educational services and a multidisciplinary team is needed to address the cognitive and emotional aspects of the population. Like teachers in any other educational system, respondents obtain some achievements and satisfactions that strengthen them spiritually and motivate them to continue working in these institutions for many years.